Risk Factors for Mortality in Refractory Pediatric Septic Shock Supported with Extracorporeal Life Support. Issue 10 (November 2020) - Workman, Jennifer K.; Bailly, David K.; Reeder, Ron W.; Dalton, Heidi J.; Berg, Robert A.; Shanley, Thomas P.; Newth, Christopher J. L.; Pollack, Murray M.; Wessel, David; Carcillo, Joseph; Harrison, Rick; Dean, J. Michael; et al.
Abstract : Risk factors for mortality in children with refractory pediatric septic shock who are supported with extracorporeal life support (ECLS) are largely unknown. Therefore, we performed univariable and multivariable analyses to determine risk factors for mortality among children (<19 years) who underwent an ECLS run between January 2012 and September 2014 at eight tertiary pediatric hospitals, and who had septic shock based on 2005 International Consensus Criteria. Of the 514 children treated with ECLS during the study period, 70 were identified with septic shock. The mortality rate was similar between those with (54.3%) and without septic shock (43.7%). Among those with septic shock, significant risk factors for mortality included cardiac failure or extracorporeal cardiopulmonary resuscitation (ECPR) as indication for ECLS cannulation compared with respiratory failure ( P = 0.003), having a new neurologic event following cannulation ( P = 0.032), acquiring a new infection following cannulation ( P = 0.005), inability to normalize pH in the 48 hours following ECLS cannulation ( P = 0.010), and requiring higher daily volume of platelet transfusions ( P = 0.005). These findings can be used to help guide clinical decision making for children with septic shock that is refractory to medical management. Abstract : Supplemental Digital Content is available in the text.